Acid and inflammatory sensitisation of naked mole-rat colonic afferent nerves. (January 2020) - Hockley, James RF; Barker, Katie H; Taylor, Toni S; Callejo, Gerard; Husson, Zoe M; Bulmer, David C; Smith, Ewan St. J
Acid sensing in the gastrointestinal tract is required for gut homeostasis and the detection of tissue acidosis caused by ischaemia, inflammation and infection. In the colorectum, activation of colonic afferents by low pH contributes to visceral hypersensitivity and abdominal pain in human disease including during inflammatory bowel disease. The naked mole-rat ( Heterocephalus glaber ) shows no pain-related behaviour to subcutaneous acid injection and cutaneous afferents are insensitive to acid, an adaptation thought to be a consequence of the subterranean, likely hypercapnic, environment in which it lives. As such we sought to investigate naked mole-rat interoception within the gastrointestinal tract and how this differed from the mouse ( Mus Musculus ). Here, we show the presence of calcitonin gene-related peptide expressing extrinsic nerve fibres innervating both mesenteric blood vessels and the myenteric plexi of the smooth muscle layers of the naked mole-rat colorectum. Using ex vivo colonic-nerve electrophysiological recordings, we show differential sensitivity of naked mole-rat, compared to mouse, colonic afferents to acid and the prototypic inflammatory mediator bradykinin, but not direct mechanical stimuli. In naked mole-rat, but not mouse, we observed mechanical hypersensitivity to acid, whilst both species sensitised to bradykinin. Collectively, these findings suggest that naked mole-rat colonic afferents are capable of detecting acidic stimuli; however, their intracellular coupling to downstream molecular effectors of neuronal excitability and mechanotransduction likely differs between species.